2020
DOI: 10.1039/c9se00812h
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical porous carbon derived from eucalyptus-bark as a sustainable electrode for high-performance solid-state supercapacitors

Abstract: Conversion of waste biomass into porous carbon, with improved energy and power, for use as an electrode for electrochemical double layer capacitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(15 citation statements)
references
References 74 publications
0
15
0
Order By: Relevance
“…11,14 In recent years, many groups reported highperformance EDLCs based on biomass-derived porous carbon electrodes. 11, 15,16 Liquid electrolytes, which are commonly used in the fabrication of supercapacitors, offer good electrode/electrolyte interfacial properties and high ionic conductivities of the order of 10 −3 −10 −2 S cm −1 , and hence, are able to provide high rate capability and capacitance to the devices. 17,18 However, they suffer from major disadvantages of corrosion, leakage, low gravimetric and volumetric energy and power densities, and bulky shapes/designs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…11,14 In recent years, many groups reported highperformance EDLCs based on biomass-derived porous carbon electrodes. 11, 15,16 Liquid electrolytes, which are commonly used in the fabrication of supercapacitors, offer good electrode/electrolyte interfacial properties and high ionic conductivities of the order of 10 −3 −10 −2 S cm −1 , and hence, are able to provide high rate capability and capacitance to the devices. 17,18 However, they suffer from major disadvantages of corrosion, leakage, low gravimetric and volumetric energy and power densities, and bulky shapes/designs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Furthermore, very few studies are reported on using eucalyptus biomass, e.g., its seeds, leaves and barks as precursors for synthesizing SC materials. [ 35–37 ] These studies followed process involving conventional high activation temperature (800 °C or higher) by treating with ZnCl 2 or with KOH. Such high temperature process was primarily aimed for achieving high surface area which are favorable for charge accumulation process via ion accessibility to the active electrode materials.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical impedance spectroscopy (EIS) measurements showed that the porous SPE has an ionic conductivity of ~10 −3 S cm −1 124 . Recently in 2020, Yadav et al 125 fabricated a symmetric SSC employing PVDF‐HFP porous SPE dipped in 0.5 M NaTFSI in EMIMTFSI and AC electrodes derived from the waste eucalyptus bark. The porous SPE was prepared by phase inversion using water as the non‐solvent bath and a solution of PVDF‐HFP in N‐Methyl‐2‐pyrrolidone (NMP).…”
Section: Electrolyte Materialsmentioning
confidence: 99%